2008
DOI: 10.1002/sia.2686
|View full text |Cite
|
Sign up to set email alerts
|

Ce 3d XPS investigation of cerium oxides and mixed cerium oxide (CexTiyOz)

Abstract: This article presents an XPS study of Ce 3d emission spectra dominated by atomic multiplet effects in core level spectroscopy of rare earth compounds (Ce oxides). Core level spectroscopy has been used to study the electronic states of Ce 3d 5/2 and Ce 3d 3/2 levels in Ce 4+ and Ce 3+ states. The well-resolved components of Ce 3d 5/2 and Ce 3d 3/2 spin-orbit components, due to various final states (4f 0 , 4f 1 , 4f 2 configurations), were determined on 3d XPS spectra from commercial powders (CeO 2 , CePO 4 ).Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

60
477
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,012 publications
(556 citation statements)
references
References 19 publications
60
477
0
4
Order By: Relevance
“…The value of the spin-orbit splitting and relative intensity is 18.4 eV and 0.57. The relative intensity and the energy separation of the peaks are in good agreement with the reported result [14,15]. As shown in Fig 1(c), composition of Ce3+ and Ce4+ is dramatically changed after annealing process.…”
Section: Resultssupporting
confidence: 90%
“…The value of the spin-orbit splitting and relative intensity is 18.4 eV and 0.57. The relative intensity and the energy separation of the peaks are in good agreement with the reported result [14,15]. As shown in Fig 1(c), composition of Ce3+ and Ce4+ is dramatically changed after annealing process.…”
Section: Resultssupporting
confidence: 90%
“…According to the literature [18][19][20][21][22][23], the four intense components v (BE ∼ 882.2 eV), u (BE ∼ 900.8 eV), v /// (BE ∼ 898.1 eV), u /// (BE ∼ 916.2 eV) as well as the two weaker components v // (BE ∼ 888.8 eV) and u // (BE ∼ 906.9 eV) can be attributed to Ce 4+ cations. For Ce 3+ cations, the v / (BE ∼ 885.6 eV) and u / (BE ∼ 903.9 eV) components are more intense, whereas the v 0 (BE ∼ 880.6-881.4 eV) and u 0 (BE ∼ 898.9-899.3 eV) components are noticeably weaker and sometimes their contributions in the Ce 3d spectrum can not be clearly distinguished, in particular at a high concentration of Ce 4+ cations [23,26,30]. In pure and multi-cation doped cerium oxides calcinated at 1350 • C, one can distinguish the contribution of the v / and u / peaks to the spectra, suggesting the presence of both Ce 4+ (major fraction) and Ce 3+ cations.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) is the method that allows monitoring changes in the local environment of ions and their oxidations states [17]. The surface chemical states of Ce cations have been explored so far preferably for undoped CeO 2 [18][19][20][21][22][23], CeO 2 -based solid solutions [24][25][26], and composites composed of CeO 2 and transition metals or their oxides [27][28][29][30][31][32][33][34]. It was shown that properties of composite materials (redox properties, formation of surface and bulk oxygen vacancies, oxygen storage and release) can be optimised through the variation of the CeO 2 /Me(Me x O y ) ratios.…”
Section: Introductionmentioning
confidence: 99%
“…O 2p → 4f transitions. 62 The Ce spectrum of Ce(III) compound is composed of four peaks corresponding to two spin-orbit features at 880.9, 885.5, 899.1 and 903.4 eV. 62 The spectrum of Ce(IV) compound is composed of six peaks corresponding to three spin-orbit features at 882.7, 886.6, 898.3, 901.3, 907.3 and 916.7 eV.…”
Section: Resultsmentioning
confidence: 99%
“…62 The Ce spectrum of Ce(III) compound is composed of four peaks corresponding to two spin-orbit features at 880.9, 885.5, 899.1 and 903.4 eV. 62 The spectrum of Ce(IV) compound is composed of six peaks corresponding to three spin-orbit features at 882.7, 886.6, 898.3, 901.3, 907.3 and 916.7 eV. It appears that prior immersion cerium is present primarily in the Ce(III) oxidation state, although some peaks may indicate the presence of small amount Ce(IV) state (i.e.…”
Section: Resultsmentioning
confidence: 99%